Leveraged ETF option strategies. Issue 5 (9th May 2016) - Trainor, William; Gregory, Richard
Abstract : Purpose: – Leveraged exchange traded funds (ETFs) have become increasingly popular since their introduction in 2006. In recent years, options on leveraged ETFs have been promoted as a means of enhancing returns and reducing risk. The purpose of this paper is to examine the interchangeability of S & P 500 ETF options with leveraged S & P 500 ETF options and to what extent these options allow investors to manage their risk exposure. Design/methodology/approach: – With increasing liquidity for these fund's options, simple option strategies such as covered calls and protective puts can be implemented. This study derives call-call and put-put parity between options on the underlying index and the associated leveraged ETFs. The paper examines comparative measures of return and risk on the underlying indices, along with covered call and protective put positions. Findings: – Using the formulations derived, this study shows options on non-leveraged ETFs or on the underlying index can be substituted for leveraged ETF options. Empirical results suggest substituting options on leveraged ETFs with options on the underlying index or index ETF give comparable results, but can differ as the realized leverage ratio over time differs from projected values. Originality/value: – This study is the first to the authors' knowledge that investigates option strategies on leveraged and inverse ETFs of equity indices. It is also the first to derive call-call and put-put parity relations between options on ETFs and related leveraged and inverse ETFs. The results contribute to securities issuance, investment strategies, and option parity relations.